PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK DI KELAS VII SMP NEGERI 2 KOTA BENGKULU - Hendrika, Eva (Jurnal Math-UMB.EDU, 2019)
This research is a classroom action research. The aim of the study is improving student’s learning achievement  on mathematics subject at class VII of SMP Negeri 2 Kota Bengkulu by using Guided Inquiry learning model. The instrument of data collection is a test for student’s learning  achievement. The subjects of the study were students of class VII A SMP Negeri 2 Kota Bengkulu concist of 33 students. The study was conducted in three cycles, in which cycles consisted of four meetings and one final test of cycle. Each cycles consist of 4 steps, namely planning, implementation, observation, reflection. The indicator of success in this study is 80% of all students who get score of ≥75. The results showed that the application of Guided Inquiry learning model can improve student’s learning achievement on mathematics. In cycle one, the average score of the students was 64.89 with classical learning completeness was 54,55%. Cycle two  the average score of the students was 78.83 with classical learning completeness was 75.76%.  The average score of the students and classical completeness was 85.76 and 87.88%. Keywords: Learning Achievement, Guided Inquiry Learning